Digestive α-L-fucosidase activity in Rhodnius prolixus after blood feeding: effect of secretagogue and nutritional stimuli - Gama, Maiara do Valle Faria; Alexandre, Yasmim do Nascimento; Pereira da Silva, João Mario; Castro, Daniele Pereira; Genta, Fernando Ariel (Frontiers in Physiology, 2023)
Rhodnius prolixus (Hemiptera: Reduviidae) is an important vector of Trypanosoma cruzi, the causative agent of Chagas Disease. This insect is a model for the study of insect physiology, especially concerning the digestion of blood. Among the enzymes produced in the midgut of R. prolixus after blood feeding there is a α-L-fucosidase activity. There are very few studies on α-L-fucosidase of insects, and the role of R. prolixus α-L-fucosidase is still not clear. In this work, we tested if the mechanism for production of this enzyme is similar to the observed for proteases, a secretatogue mechanism that respond to the protein contents of the meal. We tested if specific proteins or sugars elicit this response, which may help to understand the nature of the physiological substrate for this enzyme. In general, our results showed that the Anterior Midgut was the only midgut fraction that responds to the blood meal in terms of α-L-fucosidase production. Besides that, this response was not triggered by midgut distension or by ingestion of the blood cell fraction. Conversely, the enzyme was produced after feeding with the plasma fraction. However, the production of α-L-fucosidase was also triggered by different biochemical stimuli, as protein or fucoidan ingestion. This suggested that the production of the enzyme in the anterior midgut was a general physiological response under control of different convergent signals. Besides that, the comparison between different treatments for artificial blood feeding showed that heparinated blood was the choice with minor side effects for the study of the midgut α-L-fucosidase, when compared to defibrinated or citrated blood.